Amoxicillin-loaded chitosan/extracted collagen/elastin triple-layered scaffolds for diabetic wound healing - Ramazan, Ola; Akkad, Haya; Ciftci, Fatih; Erarslan, Azime; Ozerol, Esma Ahlatcioglu (ELSEVIER, 2026)
Chronic diabetic wounds pose a formidable clinical challenge marked by impaired healing, high infection rates, and limited efficacy of conventional therapies. In this study, we introduced a novel, multifunctional triple-layer wound dressing designed as a sophisticated in vitro platform that integrates structural support, bioactivity, and controlled drug delivery. The hierarchical system comprises a PVA-glycerol base layer, a bioactive intermediate layer composed of fish-derived collagen, chicken-derived elastin, and chitosan, and an electrospun PVA nano-fibrous top layer loaded with amoxicillin. Quantitative characterization demonstrated that the amoxicillinloaded system possesses exceptional antibacterial potency, yielding Minimum Inhibitory Concentrations (MICs) of 0.65 mg/mL against S. aureus and 2.85 mg/mL against E. coli, resulting in complete bacterial eradication within 24 h. Drug release kinetics analyzed using the Korsmeyer-Peppas equation (n = 0.62) indicated a non-Fickian (anomalous) transport mechanism, ensuring sustained therapeutic delivery over time. Mechanically, the scaffold exhibited superior robustness, with a tensile strength of 46.84 +/- 7.39 MPa in WD5, effectively mimicking the structural integrity of native skin tissue. In vitro biological evaluations using L929 fibroblast cells confirmed excellent biocompatibility and regenerative capacity. Scratch assays revealed that the triple-layered scaffold significantly accelerated cell migration and gap closure compared to control groups, while longitudinal assessments over 1, 7, and 14 days demonstrated continuous and accelerated cell proliferation. The novelty of this platform lies in the synergistic integration of sustainable biomaterials, a hierarchical architecture, and precisely controlled drug delivery. While these preliminary in vitro findings offer promising proof-of-concept for chronic wound management, further in vivo and clinical studies are essential to assess the scaffold's full translational potential for diabetic wound healing.
Keywords: Amoxicillin release kinetics; Chicken-derived elastin; Diabetic foot ulcer; Electrospun nanofibers; Fish skin collagen; Multilayer scaffold; Sustainable biomaterials; Wound healing; IN-VITRO; ELASTIN; MATRIX; Pharmacology & Pharmacy